Morphological Characterization of Plant-parasitic Nematodes in Livistona rotundifola - Fernando, Norma; Kooragoda, Mewan (Advances in Technology, 2022)
Livistonia rotundifola also known as ‘table palm’ or ‘fan palm’ is one of the major export foliage plant in Sri Lanka. The exportation has a potential to generate income for the medium scale farmers. The plants are mainly exported at size 25-85cm potted plants to Germany, USA, Japan, China, and Switzerland according to the data reports ‘’Anonymous [1]’’. Recently some shipments have been rejected due to infestation with parasitic nematodes at National plant quarantine service ,Sri Lanka.